Towards a formally verified microkernel using the Frama-C toolset - Carloto, Carlos José Abreu Dias da Silva (2015)
Submitted by Joana Lopes Dias (jdias@ubi.pt) on 2015-07-15T09:44:06Z No. of bitstreams: 1 Dissertação - Carlos José Abreu Dias da Silva Carloto.pdf: 2226070 bytes, checksum: 7add40c398a10c3614e837434a325ce0 (MD5)